Liturgi: Menumbuhkan Harapan dan Pembebasan - Kusuma, Yoseph Indra (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
This study examines the role of liturgy in fostering hope and liberation within the Catholic faith, inspired by Romano Guardini’s The Spirit of the Liturgy. Liturgy is often misunderstood in two extremes: as rigid rules that restrict spiritual freedom or as a celebration devoid of structure. This research aims to explore liturgy as a